3D printing of fine-grained aluminum alloys through extrusion-based additive manufacturing: Microstructure and property characterization. (10th March 2023) - Liu, Fengchao; Dong, Pingsha; Khan, Abdul Sayeed; Zhang, Yuning; Cheng, Randy; Taub, Alan; Ma, Zongyi
Highlights: A new extrusion-based solid-state metal additive manufacturing method was developed. The new method enables direct deposition of fine-grained aluminum alloy without melting. The new method uses off-the-shelf metal rods rather than pricy powders as feedstock. The printing process was completed in an open-air environment, avoiding costly inert or vacuum conditions. The printed 6061 aluminum alloys yield the strength and ductility comparable to wrought 6061 aluminum alloys. Abstract: Additive manufacturing (AM) has the potential to transform manufacturing by enabling previously unthinkable products, digital inventory and delivery, and distributed manufacturing. Here we presented an extrusion-based metal AM method (refer to "SoftTouch" deposition in the filed patent) that is suitable for making the metal feedstock flowable prior to the deposition through dynamic recrystallization induced grain refinement at elevated temperatures. The flowable metal was extruded out of the printer head like a paste for building dense metal parts with fine equiaxed grains and wrought mechanical properties. Off-the-shelf metal rods were used as feedstock and the printing process was completed in an open-air environment, avoiding pricy powders and costly inert or vacuum conditions. The resulting multi-layer deposited 6061 aluminum alloys yield strength and ductility comparable to wrought 6061 aluminum alloys after the same T6 heat treatment. The extrusion-based metal AM method can also be advanced as green manufacturing technologies for fabricating novel alloys and composites, adding novel features to existing parts, repairing damaged metal parts, and welding advanced metals for supporting sustainable manufacturing, in addition to being developed into a cost-effective manufacturing process for the fabrication of dense metal of complex structural forms. Graphical abstract: Image, graphical abstract